Moral Values in Jerry Spinelli’s Stargirl - Rizka Nur Amaliyah A.; Abdur Rohman; Machfud Muhamad Sodiq; Ahmad Frank; Abu Fanani (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The aim of this study is to depict the moral values of Susan Caraway that turns into the name of Stargirl in Jerry Spinelli’s Stargirl. Susan Caraway is a school student who wants to get popularity by the name of Stargirl. Though she gets her dream of being popular, yet, she shows her moral values to her friends. Using a qualitative descriptive method and descriptive and dramatic method as well as Robert Audi’s theory of moral values, and by explaining the main character’s moral values, quoting the related quotation in the novel about the moral values, and analyzing the quotation related to the theory, then the researcher herself as the instrument of the study finds that Susan Caraway shows her moral values such as beneficence, honesty, and gratitude. Beneficence, then, is separated into having positive thinking, being responsible, and having self-control. Honesty is performed in the form of not being a lier, whilst, gratitude is performed in the form of appreciation other’s goodness.